Improving the Management of Terminal Delirium at the End of Life - Megan Sutherland; Aakriti Pyakurel; Amy E Nolen; Kalliopi (Kalli) (Elsevier, 2020)
Objective: Terminal delirium is a distressing process that occurs in the dying phase, often misdiagnosed and undertreated. A hospital developed the "comfort measures order set" for dying patients receiving comfort care in the final 72 h of life. A chart review of patients experiencing terminal delirium revealed that the current medication option initially included in the order set was suboptimally effective and patients with terminal delirium were consistently undertreated. The purpose of this pilot study was to highlight an in-service intervention educating nurses on the management of terminal delirium at the end of life and to assess its effect on their knowledge of the management of patients with terminal delirium. Methods: A before-and-after survey design was used to assess the effect of the in-service training on nurses' knowledge of terminal delirium. Results: We describe the results from a small sample of nurses at a large urban tertiary care center in Canada. Of the twenty nurses who attended the in-services, 60% had cared for a patient with terminal delirium; however, 50% felt that their knowledge of the topic was inadequate. Despite no statistical significance between the pre- and posttest scores for both the oncology and the medicine unit nurses, all participants who completed posttest survey found the in-services useful. Conclusions: The findings from this study provide initial insights into the importance of in-service trainings to improve the end-of-life care and nursing practice. Future research will include expanding this pilot project with sufficient power to assess the significance of these types of interventions.